2007
DOI: 10.1299/jtst.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stretch on Local Burning Velocity of Premixed Turbulent Flames

Abstract: The effect of positive stretch on the local flame properties of turbulent propagating flames in the flamelet regime was investigated experimentally for methane-, hydrogen-and propane-air mixtures with lean and rich having nearly the same laminar burning velocity (S L0 =25cm/s). The ratio of the turbulence intensity u' to S L0 was varied as 1.4 and 2. A 2D laser tomography technique was used to obtain the temporal local flame configuration and movement in a constant-volume vessel. Some of the key parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…4 that the values of η 0 /r, Ka T and S F are distributed over a wider range than those obtained in the laminar combustion (20), (26) , even under u'/S L0 =1.4. Additionally, the same interesting tendencies as those in previous studies (20), (26) can be observed from Figure 6 shows the variation of the mean value of S F on the whole flame front S F,m normalized by S L0 with δ H , Φ and fuel types. It is clear from Fig.…”
Section: Local Flame Displacement Velocitymentioning
confidence: 68%
See 4 more Smart Citations
“…4 that the values of η 0 /r, Ka T and S F are distributed over a wider range than those obtained in the laminar combustion (20), (26) , even under u'/S L0 =1.4. Additionally, the same interesting tendencies as those in previous studies (20), (26) can be observed from Figure 6 shows the variation of the mean value of S F on the whole flame front S F,m normalized by S L0 with δ H , Φ and fuel types. It is clear from Fig.…”
Section: Local Flame Displacement Velocitymentioning
confidence: 68%
“…In our previous study (26) , it was obtained that there was a meaningful relationship between S F of turbulent flames and Markstein number Ma of laminar flames. So, this section examines the relation between S F and Ma.…”
Section: Effect Of Positive Stretch Due To Markstein Number On the Lomentioning
confidence: 89%
See 3 more Smart Citations